Diagnóstico y propuesta de un modelo de gestión administrativa a la empresa “Agua D’lago” del cantón Lago Agrio para el año 2015 - Arellano Ninabanda, María Perpetuo (2016)
The proposal of the study, administrative management model, was created with the purpose of developing domestic capacities in the company; processes, and procedures, defining workflow processes, administrative, production, sales and marketing, standardize processes and document the processes for each activity, also determined the key processes inside the company, allowing to develop capabilities that ensure control and continuous improvement processes. At the stage of establishment of processes and procedures, described a table which shows the payroll of workers, the position they currently occupy and the definition of the process assigned to each activity, then structured the functional organization of the company, thus structuring the objectives achieved basic responsibilities individual group of processes. All of this based on the information that was obtained from the surveys develop, interviews and observation of the company. In addition this information were to make a diagnosis situational company applying FODA matrix, describing the strengths, opportunities, weaknesses and threats, is qualified and weighted to get a baseline and set strategies, also generated matrixes for the definition of the Vision, mission, principles, organizational. In addition to this, established the key processes of the company, these are: process of production, process of maintenance of production equipment, process of packaging containers and cases. These processes, which are defined as keys because they are directly related to the production and the quality of the product The definition of the model of administrative management by processes such as proposal for the Agua D’ Lago company, develops in the literal 'g' discussion, with the construction of a table that are described; The macro process, payroll workers, charge, procedure, process, and code, in this table are organized the activities of managers and employees, in accordance with the activities and assigned departments such which were working but unaware of the processes and the description of the procedures. The purpose of the above described, is intended to articulate in a matrix description of processes, in which are defined: process, procedure, responsible for, the aim of the process, the scope, the description of the process, resources, inputs and outputs, activities, a description of these activities, responsible and expected standard of quality product, indicators, control points. Then, as the management model, proposes the design of flow grasses by each process, thus also proposes matrix description of activities, description of processes and process map. This being the final stage of administrative management model process and procedures Research methodology, allowing to collect information, primary and secondary schools, has been used in the study process techniques used for this purpose, was the scientific method: inductive, deductive, descriptive was used as data collection techniques: literature review, surveys, interviews, direct observation of field. In conclusion, the model of administrative management for the Agua D´ Lago company, will establish a design work, which will optimize the resources of the company, using a model of processes and procedures, described in flow diagrams, matrices of process, procedure and process maps, established for the company a manual for the development of the activities to be carried out in each Department , describing the activities to be undertaken every employee at your workplace, obtaining in this way a better performance per employee, this was reflected in an economic increase for the company, decrease in labour disputes, proper allocation of activities, improved performance in production and standardization of processes and procedures.